Seroprevalence of SARS-CoV-2 IgG in blood donors in a teaching institute from Western part of Maharashtra - Rajashri A. Patil; Nikunja K. Das; Nageswari R. Gandham; Chanda Vyawahare; Jyoti Ajagunde; Sameena Khan; Parag J. Ratnakar; Yamini Ingle (Journal of Family Medicine and Primary Care, 2024)
Introduction: COVID-19 is a disease caused by the severe acute respiratory syndrome coronavirus 2 that has appeared as a global pandemic in recent times. Currently, the transmission rate has slowed down significantly, but the definite pathological reason behind this is still unknown. Therefore, the prevalence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody must be studied to establish the relation between the rate of transmission and antibody presence. Materials and Methods: A clinical assessment was performed to evaluate the seroprevalence of SARS-CoV-2 Immunoglobulin G (IgG) antibodies among 299 healthy volunteers in the period of February to May 2021. Serum samples were analyzed using chemiluminescent microparticle immunoassay (CMIA) technology to detect the presence of IgG antibodies. Result: It was observed that 21% of the participants were seropositive, and 78% of the population was seronegative across the different genders. This confirmed that the generation of antibodies is independent of gender. Simultaneously, a t-test was performed that further suggested no statistical correlation between gender and seroprevalence. Moreover, a comprehensive analysis was performed to establish the relation between age and blood group with the seroprevalence. However, there was no statistical relationship found among these parameters. Conclusion: This study assisted in examining the underlying causes of high or low seroprevalence among healthy volunteers.